Direct injection of HILIC fractions on the reversed‐phase trap column improves protein identification rates for salivary proteins. Issue 22 (10th October 2016) - Fichtenbaum, Andreas; Schmid, Rainer; Mitulović, Goran
Abstract : Online combination of hydrophilic interaction chromatography (HILIC) and RP chromatography for separation of tryptic peptides is a challenging approach due to the incompatibility of direct loading HILIC fractions on the RP trapping column. High amounts of organic modifiers in loading solvents decrease the binding efficiency of tryptic peptides on C18 phases and lower the number of identifications. A 500 μL loop upfront of the trapping column filled with aqueous mobile phase was employed as a mixing chamber and enabled direct injections and improved saliva protein identification rates of HILIC fractions.